Prosthetic obturators used in the treatment of cystic jaw bones - Loster , Jolanta; Ryniewicz, Wojciech; Gala , Andrzej; Wieczorek , Aneta (Journal of Stomatology, 2015)
Patients diagnosed with cystic lesions of the jaw bones undergo surgical treatment consisting in decompression and curettage due to the extent of lesions. Prosthetic obturator is used between stages of treatment. Aim of the study. To analyse a group of patients and to present the prosthetic procedure with the use of obturators. Material and methods. The analysis covered a group of patients treated from 01.07.2011 to 31.12.2012. The data included demographic data, location of lesion, histopathological diagnosis, the type of obturator and the duration of treatment. Results. The analysis covered 102 subjects. In 68 patients the lesions were located in the mandible. Histopathological diagnosis was dominated by odontogenic and dentigerous cysts (in 38 cases). In all the cases, a prosthetic obturator was used. The second stage of surgical therapy was performed in 75 cases. Conclusion. The application of obturator in the treatment of patients with cysts plays an important role.